2008
DOI: 10.1097/iae.0b013e31815ec275
|View full text |Cite
|
Sign up to set email alerts
|

Human Idiopathic Epiretinal Membranes Express NGF and NGF Receptors

Abstract: Idiopathic ERMs were characterized by myoFBs. The expression of NGF, trkA, and p75 in local myoFBs associated with changes in ERM vitreous NGF suggests an involvement of NGF, as previously reported for TGF-beta1, in the evolution and myoFB-mediated contractile activity of ERMs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 23 publications
4
26
0
1
Order By: Relevance
“…According to previous reports, Müller glial cells and myofibroblasts constituting iERM tissues were positive for glial fibrillary acid protein (GFAP) and α-smooth muscle actin (α-SMA), respectively81516. Double labeling experiments revealed co-localization of (P)RR signal with GFAP, a glial cell marker (Fig.…”
Section: Resultssupporting
confidence: 58%
See 2 more Smart Citations
“…According to previous reports, Müller glial cells and myofibroblasts constituting iERM tissues were positive for glial fibrillary acid protein (GFAP) and α-smooth muscle actin (α-SMA), respectively81516. Double labeling experiments revealed co-localization of (P)RR signal with GFAP, a glial cell marker (Fig.…”
Section: Resultssupporting
confidence: 58%
“…Among them, Müller glial cells, a main constituent cell type in iERM, are the most important cellular components required for membrane growth by intracellular signal transduction1519. Several studies described the involvement of cytokines and trophic factors in the pathogenesis of iERM4816212223. Stimulation of fibroblasts with Ang II are known to promote collagen synthesis24; however, little is known about whether this is the case with Müller glial cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…24,30 Transforming growth factor-b-1 and the nerve growth factor were shown to play a crucial role in fibroblast activities and were detected in the vitreal humor of each of the eight patients with idiopathic ERMs. 30 Kohno et al 25 demonstrated that TGF-b-2 stimulates the differentiation of hyalocytes into myofibroblasts. Interestingly, Zhao et al 31 reported hyalocytes and retinal Müller cells to be the predominant cell types in idiopathic ERMs.…”
Section: Discussionmentioning
confidence: 99%
“…This may be explained by tractional forces associated with ERM development and progression. 13 Contraction of the membrane exerts tangential traction on the inner retina and overlying vessels, making retinal vessels crowd toward the contraction center. 10 Thus, a smaller preoperative AUV may indicate more macular contraction caused by ERM.…”
Section: Eyementioning
confidence: 99%